2021
DOI: 10.21203/rs.3.rs-136115/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Curcumin and its analog alleviate diabetes-induced damages by regulating inflammation and oxidative stress in brain of diabetic rats​

Abstract: Background: Diabetic encephalopathy is a severe diabetes complication with cognitive dysfunction and neuropsychiatric disability. The mechanisms underlying diabetic encephalopathy is believed to be relevant with oxidative stress, vascular amylin deposition, immune receptors, inflammation, etc. This study wanted to evaluate the ability of curcumin and its analog A13 to alleviate oxidative stress and inflammation in diabetes-induced damages in brain. Methods: Sixty adult male Sprague-Dawley rats were divided int… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…49 Similarly, other studies revealed that curcumin decreased oxidative stress and inflammation via different pathways. [50][51][52] Based on all the animal studies, diabetic patients receiving curcumin support had an improvement in their metabolic parameters. Curcumin shows anti-diabetic effects with its properties such as anti-inflammatory, anti-oxidant, anti-hyperglycaemic, and anti-hyperlipidaemic.…”
Section: Food and Function Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…49 Similarly, other studies revealed that curcumin decreased oxidative stress and inflammation via different pathways. [50][51][52] Based on all the animal studies, diabetic patients receiving curcumin support had an improvement in their metabolic parameters. Curcumin shows anti-diabetic effects with its properties such as anti-inflammatory, anti-oxidant, anti-hyperglycaemic, and anti-hyperlipidaemic.…”
Section: Food and Function Reviewmentioning
confidence: 99%
“…It was found that curcumin can improve diabetic complexities by modulating a range of critical signal steps in disease prognosis and reducing pro-inflammatory and proapoptotic cytokines and transcription factors such as TNF-α and NF-κB. 51 It is well known that both hyperglycemia and advanced glycation end products (AGEs) can lead to tissue oxidative stress, causing loss of homeostasis. The protective effect of curcumin against the formation of diabetes-induced AGEs was first demonstrated in 1998.…”
Section: Anti-hyperglycaemic Effectsmentioning
confidence: 99%
See 2 more Smart Citations